2012
DOI: 10.1111/j.1442-2018.2012.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Grief reaction model of families who experienced acute bereavement in Japan

Abstract: The present study clarified the structure of factors that affect grief reactions of families who experienced acute bereavement in critical care settings in Japan. Sixty-four families who experienced acute bereavement answered a questionnaire. The questionnaire included the Miyabayashi Grief Measurement, recognition of bereavement, Multidimensional Scale of Perceived Social Support, and the Tri-Axial Coping Scale. We analyzed the causal structure regarding the relationship of stress recognition, coping, and gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…We found perceived stress was positively and directly correlated with PGD symptoms. The finding is consistent with a prior research documenting that when the families who undergo acute bereavement felt more stress about this bereavement, they would tend to suffer stronger grief reactions [25]. Our finding is also in line with the stress and coping theory [27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found perceived stress was positively and directly correlated with PGD symptoms. The finding is consistent with a prior research documenting that when the families who undergo acute bereavement felt more stress about this bereavement, they would tend to suffer stronger grief reactions [25]. Our finding is also in line with the stress and coping theory [27].…”
Section: Discussionsupporting
confidence: 93%
“…The death of a close person is one of the most stressful experiences in one’s life, which can seriously affect physical and mental health [ 25 ]. Perceived stress reflects an individual’s global subjective evaluation to the stress level which caused by objective events [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with findings from previous research, which refers to this form of memory transmission in Japanese society as ‘cherished reminiscence’ of the deceased [ 21 , 22 ]. Cherished reminiscence has previously been investigated as an aspect of the mourning process which may facilitate adjustment to loss [ 35 , 36 ]. The interviews from this study support these findings, as participants reflect that their positive remembrance of the deceased leaves them feeling connected, hopeful, and at peace.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ozanne, Graneheim, and Strang (2015) found that the spouses of demanding people with chronic neuromuscular disease were mourning and struggling in finding meaning in life after the partner's death. A study in Japan noted that the severe grief reaction of the family depended on the quality of dying and death and a peaceful death (Tatsuno, Yamase, & Yamase, 2012).…”
Section: Discussionmentioning
confidence: 99%